Evaluation of climate variability impact on sources of water supply - Olanrewaju, R. M.; Adedoyin, F.; Akpan, G. P. (Penerbit Universiti Kebangsaan Malaysia, 2019)
Climate is a key factor in water availability and accessibility on both the earth surface and below the earth surface. The study evaluated climate variability impact on sources of water supply in Offa, Kwara State, Nigeria. The study utilized both primary and secondary source of data. Household proximity to water sources was computed using the percentages of household that falls within the basic indicator for measuring water access by World Health Organization. Correlation and multiple regression analyses were used to determine the relationship between the climatic variables and water supply; and groundwater level in the study area. Pearson Product Moment Correlation was employed to establish the association between climate and water supply; and groundwater level. Multiple regression analysis was used to examine the relationship between water supply and the selected climatic variables. Trend analysis was used to determine the trend of the selected climatic variables in the study area. The result revealed that rainfall amount, minimum and maximum temperature, and evaporation exhibit an upward trend which are not statistically significant. The fluctuating trend in these climatic variables, though not statistically significant are probably related to the already established changes in climatic parameters in Nigeria. The result also showed that the spatial distributions of public boreholes in the study area are heterogeneous in nature. The study recommended that the clustering of water sources, especially the shallow wells should be discouraged to avoid over abstraction of groundwater in the study area.